Highly Efficient Inverted Circularly Polarized Organic Light-Emitting Diodes - Wan,L; Wade,J; Shi,X; Xu,S; Fuchter,MJ; Campbell,AJ (ACS Applied Materials & Interfaces, 2020)
Circularly polarized (CP) electroluminescence has been demonstrated as a strategy to improve the performance of organic light-emitting diode (OLED) displays. CP emission can be generated from both small-molecule and polymer OLEDs (SM-OLEDs and PLEDs), but to date, these devices suffer from low dissymmetry factors (g-factor < 0.1), poor device performance, or a combination of the two. Here, we demonstrate the first CP-PLED employing an inverted device architecture. Through this approach, we demonstrate a highly efficient CP-PLED, with a current efficiency of 16.4 cd/A, a power efficiency of 16.6 lm/W, a maximum luminance of over 28,500 cd/m2, and a high EL dissymmetry (gEL) of 0.57. We find that the handedness of the emitted light is sensitive to the PLED device architecture: the sign of CP-EL from an identically prepared active layer reverses between inverted and conventional devices. The inverted structure affords the first demonstration of CP-PLEDs exhibiting both high efficiency and high dissymmetry—the two figures of merit which, until now, have been difficult to achieve at the same time. We also highlight device architecture and associated internal electric field to be a previously unexplored means to control the handedness of CP emission. Our findings significantly broaden the versatility of CP emissive devices and should enable their further application in a variety of other CP-dependent technologies.